Deaths of drug addicts in the United Kingdom 1967-81. Issue 6466 (9th February 1985) - Ghodse, A H; Sheehan, M; Taylor, C; Edwards, G
Abstract : A search of the Home Office index of notified drug addicts identified 1499 deaths during 1967-81, of which 226 (15%) were of therapeutic addicts–that is, patients who had become addicted during medical treatment with a notifiable drug–and 1273 (85%) were of non-therapeutic addicts. The crude mortality fell from 23.5/1000/year for the period 1968-70 to 18.4/1000/year for 1978-80. Altogether 416 addicts aged under 50 at notification died after 1972, which was 16 times the number of deaths expected in a population with a similar age and sex composition. A more detailed examination of the cohorts of addicts notified each year showed little variation between them in the first two years of follow up. Nineteen addicts (1.6%) had died by 31 December of the year of their notification and 39 (3.3%) one year later. These figures may be an indication of the clinical course of addiction. Most deaths of non-therapeutic addicts in which a drug was implicated (939 cases (74%] were due to medically prescribed drugs–barbiturates at first and later opiates such as dipipanone hydrochloride and dextromoramide. Heroin was implicated in only 65 (7%) of these deaths. The Home Office index is a valuable source for identifying drugs of abuse and serious problems of addiction. The fact that prescribed drugs are causing the death of so many addicts demands a response from the medical profession.